Development of the integrated management system in food production company - Vayskrobova E.; Baryshnikova N.; Reznichenko I.; Pokramovich L. (Техника и технология пищевых производств)
Modern tendencies in food industry development (including meat products processing) are connected with compulsory advance and improvement in production techniques as well as implementation of effective management systems which stem from the integrated approach to risk management. The development and implementation of the systems which would guarantee required and stable safety of products for consumers are very important as well as their quality. For that reason it is essential to develop the models of integrated management system which will be based on the quality management system (QMS) and food safety management system standards. The authors performed comparative analysis of the requirements of the integrated standards. As a result of the analysis and expert evaluation they determined ten areas of integration, developed the matrix of requirements for the elements of the integrated system. The authors studied the risks, gave scientific evidence concerning the occurrence of potential hazards, determined unacceptable risks, pointed out critical control points and developed food safety management system plan for management in these points. They also determined the regularities in the influence of the quality loop stages on the quality and safety parameters, identified and structured the processes using IDEF0 function modeling methodology, made the blocks of graphs that show the interaction of processes determining the directions of information and product flows and reflecting the interaction of processes. The authors developed an integrated system model and determined the information requirements for its functioning. They used the procedure of the system performance assessment in a company using self-assessment criteria. The authors showed the advantages of the implementation and improvement of the integrated system in the company located in Saransk, the Republic of Mordovia.